Investigating Politeness Strategies Among Native Indonesian Speakers During Presidential Candidate Debate: A Cyberpragmatic Study - Shilva Lioni; Tri Pujiati (Journal of Digital Sociohumanities)
Politeness on social media is an important on speaking in the cyberspace. Language speech in cyberspace needs to receive attention so that the language used can be accepted among society, especially  in Indonesia who are oriented towards Eastern culture with the politeness be the important issue to be discussed. Studies on media related to politeness strategies using the Cyberpragmatic approach in presidential candidate debates is still rarely to conduct especially the research that provided the role of context such as speaker cultural background and condition influencing the expression of utterance. To adress this gap, our research with a qualitative descriptive design seeks to see the impression of politeness strategies used by native Indonesian speaker in Twitter during the fourth of 2024 presidential candidate debate. Our findings revealed that the use of politeness strategies was found give the impression that the choice of politeness strategies in commenting on social media needs to be considered among the native Indonesian speaker when using social media so that the speech  conveyed does not cause controversy and can be accepted by other language users involved in virtual communication which in return helps to build quality relationships and keeps them as Indonesian which have good at attitude, communicative competence, and beliefs.